2012
DOI: 10.1016/j.crohns.2011.11.009
|View full text |Cite|
|
Sign up to set email alerts
|

Results of the 2nd Scientific Workshop of the ECCO (III): Basic mechanisms of intestinal healing

Abstract: The second scientific workshop of the European Crohn's and Colitis Organization (ECCO) focused on the relevance of intestinal healing for the disease course of inflammatory bowel disease (IBD). The objective was to better understand basic mechanisms, markers for disease prediction, detection and monitoring of intestinal healing, impact of intestinal healing on the disease course of IBD as well as therapeutic strategies. The results of this workshop are presented in four separate manuscripts. This section descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 140 publications
1
40
0
5
Order By: Relevance
“…In the last few years, clinical data have shown that promoting mucosal healing plays a key role in inducing and maintaining remission in Crohn's disease or ulcerative colitis patients [25]. Therefore, from a clinical perspective, we agree with the proposal by Hunter et al [18] that injections of M0 or M2 macrophages into these patients may indeed promote mucosal healing in the short or long term, alone or in combination with conventional therapies.…”
Section: Discussionsupporting
confidence: 58%
“…In the last few years, clinical data have shown that promoting mucosal healing plays a key role in inducing and maintaining remission in Crohn's disease or ulcerative colitis patients [25]. Therefore, from a clinical perspective, we agree with the proposal by Hunter et al [18] that injections of M0 or M2 macrophages into these patients may indeed promote mucosal healing in the short or long term, alone or in combination with conventional therapies.…”
Section: Discussionsupporting
confidence: 58%
“…Although this effect is highly desirable as a response to acute tissue injury, in cases of persistent inflammation, as in IBD, it might become deleterious. In patients with CD, chronic or excessive wound healing results in fibrostenotic lesions, a major indication for surgery, whereas, in patients with ulcerative colitis, it may cause colon shortening and dysmotility (39). As such, from a therapeutic perspective, blocking MCH might prevent such complications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the ROS and reactive nitrogen species (RNS), produced during inflammation, contribute to the creation of a hypoxic milieu [11]. In 2003, Giatromanolaki et al [14] compared the expression of HIF1α and HIF2α with the expression of the angiogenic factors thymidine phosphorylase, VEGF, and VEGF-KDR in surgical specimens from patients with active UC and CD.…”
Section: Gut Microbiota Sustains Intestinal Damagementioning
confidence: 99%
“…Finally, this portrait is completed by Paneth cells with their antimicrobial peptides (i.e. defensins, REG proteins) and goblet cells that produce mucins and support, overall, cells proliferation, expansion and differentiation [10,11]. …”
Section: Mechanism Of Mucosal Injury and Mh Within The Gutmentioning
confidence: 99%
See 1 more Smart Citation